2019
DOI: 10.1021/acs.jafc.9b02172
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Acquisition of Fusarium oxysporum f. sp. niveum Toxin-Deficient Mutant and Its Effects on Watermelon Fusarium Wilt

Abstract: Watermelon Fusarium wilt is a common soil-borne disease that has significantly affected its yield. In this study, fusaric acid-deficient mutant designated as ΔFUBT (mutated from Fusarium oxysporum f. sp. niveum, FON) was obtained. The ΔFUBT mutant showed significant decrease in fusaric acid production but maintained wild-type characteristics, such as in vitro colony morphology, size, and conidiation. A field pot experiment demonstrated that ΔFUBT could successfully colonize the rhizosphere and the roots of wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…cucumerium and F. oxysporum f. sp. niveum, 4,5 and stem blight of asparagus caused by Phomopsis asparagi (P. aragi). 6 At the same time, some marine phytoplankton species (microalgae), such as Amphidinium carterae (A. carterae), Heterocapsa circularisquama (H. circularisquama), Heterosigma akashiwo (H. akashiwo), and Prorocentrum donghaiense (P. donghaiense), can often cause red tides that do harm to the development of mariculture.…”
Section: ■ Introductionmentioning
confidence: 99%
“…cucumerium and F. oxysporum f. sp. niveum, 4,5 and stem blight of asparagus caused by Phomopsis asparagi (P. aragi). 6 At the same time, some marine phytoplankton species (microalgae), such as Amphidinium carterae (A. carterae), Heterocapsa circularisquama (H. circularisquama), Heterosigma akashiwo (H. akashiwo), and Prorocentrum donghaiense (P. donghaiense), can often cause red tides that do harm to the development of mariculture.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Another approach is using non-pathogenic F. oxysporum, which antagonizes the pathogenic Fo or primes host immune response. Therefore, understanding the pathogenesis and virulence of Fo is pivotal in controlling Fusarium wilt in the field [6].…”
Section: Introductionmentioning
confidence: 99%
“…Mycotoxins from fungi are key factors on the process of establishment of infection in plants, and fusaric acid from F. oxysporum may interfere on metabolic pathways of host plant during invasion process [35]. Recently, a study with fusaric acid-deficient mutant was evaluated and showed to increase the resistance in watermelon by Fusarium proliferation [39].…”
Section: Resultsmentioning
confidence: 99%